Employee Relations at PT ASDP Indonesia Ferry (Persero) Bakauheni Branch Office in Supporting Employees Work Spirit - Maharani, Apriyana; Andryani, Kristina; Mutiara, Mutiara (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the company's efforts in implementing programs that can support its employees and the method used in this research is qualitative descriptive by conducting interviews, documentation and observation with reference to employee relations theory. This method is used to obtain the results of implementing employee relations at PT ASDP Indonesia Ferry (Persero) Bakauheni Branch Office in Supporting Employee Work Morale. As for the results of employee relations carried out at PT ASDP Indonesia Ferry (Persero) Bakauheni Branch Office, there are various activities such as educational scholarships, K3 training, motivator seminars, Ferryzi ambassadors, Ferryzi Talent Development, Ferryzi awards, long service awards, employee sons and daughters awards, Management meetings, Mading, RKAC, Gymnastics, Customers Day, PHBI, and others and the role of the HR & General work unit in helping to collect employee aspirations regarding what is needed. So that the implementation of employee relations activities is not fully controlled by management, therefore the programs that have been implemented can be considered effective because employees can feel the benefits received.